THE DEVELOPMENT OF A DEVELOPMENT ECONOMICS TEXTBOOK TO IMPROVE THE QUALITY OF LEARNING IN THE DEVELOPMENT ECONOMICS COURSE IN THE ECONOMIC EDUCATION STUDY PROGRAM - Andriansyah, Eka Hendi; Subroto, Waspodo Tjipto; Prakoso, Albrian Fiky (IKIP Widya Darma, 2023)
Improving the quality of learning should be pursued continuously, covering various factors that support improving student learning outcomes. Study Materials or Learning Materials are one of the dominant factors in improving the quality of learning. (Guide to Preparing Higher Education Curriculum in the Industrial Era 4.0 to support MBKM, 2020). Learning materials include reference books, monographs, diktats, modules, videos, practical instructions, textbooks, and other equivalent learning resources. As explained in the MKBM for the Economic Education Study Program, there are 23 courses in the field of science and expertise and 8 basic courses, and in general, they are not supported by textbooks that follow the Semester Learning Plan (SLP) of the courses. These conditions make it urgent that textbooks for each course are necessary to improve the quality of the learning process and outcomes of the course concerned, especially in efforts to achieve graduate learning outcomes (GLO). This research aims to develop a Development Economics textbook to support adequate and appropriate learning of Development Economics courses. The research method used is the research and development (Research and Development) ADDIE development model with five stages, namely analysis (analysis stage), design (design stage), development (development stage), implementation (implementation stage), and evaluation (evaluation stage). The targeted output is to produce a Development Economics textbook that has an ISBN and Intellectual Property Rights (IPR).